1998
DOI: 10.1523/jneurosci.18-22-09471.1998
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Vagal Afferents after Intravenous Injection of Interleukin-1β: Role of Endogenous Prostaglandins

Abstract: Intravenous administration of interleukin-1 (IL-1) activates central autonomic neuronal circuitries originating in the nucleus of the solitary tract (NTS). The mechanism(s) by which bloodborne IL-1 regulates brain functions, whether by operating across the blood-brain barrier and/or by activating peripheral sensory afferents, remains to be characterized. It has been proposed that vagal afferents originating in the periphery may monitor circulating IL-1 levels, because neurons within the NTS are primary recipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
251
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(260 citation statements)
references
References 72 publications
5
251
0
4
Order By: Relevance
“…Thus, it has been reported that vagal afferents express IL-1R1 (Ek et al, 1998) and that they mediate behavioral responses to immune challenge (Maier et al, 1998). Moreover, blockage of neural signaling in somatic nerves by local anesthesia has been shown to abolish centrally elicited responses to peripheral immune challenge (Belevych et al, 2010;Roth and De Souza, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been reported that vagal afferents express IL-1R1 (Ek et al, 1998) and that they mediate behavioral responses to immune challenge (Maier et al, 1998). Moreover, blockage of neural signaling in somatic nerves by local anesthesia has been shown to abolish centrally elicited responses to peripheral immune challenge (Belevych et al, 2010;Roth and De Souza, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both the magnitude and duration of LPS-induced inhibition of social investigation were greater in long-day as compared to short-day rats. The primary mediators of LPS-induced sickness behaviors are IL-1β, IL-6 and TNFα, which act both in the periphery and in the CNS to regulate ingestive behavior and emotional tone (Kent et al, 1992;Ek et al, 1998;Quan et al, 1998;Konsman et al, 2000;Dantzer et al, 2001). The present results suggest that functionally-significant aspects of this immune-neural pathway may be altered following adaptation to short photoperiods.…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine actions may include directly producing discharge of nerve fibers. [25][26][27] The slow pathway starts with cytokine production by macrophages that can act on the circumventricular organs (CVOs) and choroid plexus surrounding brain ventricles. These regions have no blood-brain barrier.…”
Section: Preclinical Evidence Consistent With Roles For Cytokines In mentioning
confidence: 99%